A comparison of two seabird communities on opposite coasts of the Alborán Sea (western Mediterranean) - Paracuellos, Mariano; Jerez, Diego (Scientia Marina, 2003)
We compared the seabird communities at two sites of the southern and northern shores of the Alborán Sea in the Western Mediterranean (Melilla and Adra respectively) during a whole year. Similarities and differences in environmental characteristics of the two study sites were caused by a set of geographical, physical and socio-economic human factors. Sampling was performed weekly during two-hour periods by counting seabirds crossing a given point of the coast. We found similarities in the composition and seasonality of the species between Melilla and Adra. However, there were differences between the two sites in the number of species and individuals, which were usually higher on the southern shore. In this area, seabirds depending on marine trophic resources were more abundant, whereas on the northern shore the most abundant seabird species were those whose feeding habits were not so dependent on sea resources.